On six poorly known species of Thomisidae (Arachnida: Araneae) described by Ludovico di Caporiacco - Marusik, Yuri M. (Zootaxa, 2025)
Illustrations are provided for the type material of six species described by Caporiacco: Heriaesynaema flavipes Caporiacco, 1939; Oxytate jannonei (Caporiacco, 1940); and Synema variabile Caporiacco, 1939 from Ethiopia; Misumenoides rubrithorax Caporiacco, 1947; and Misumenops candidoi (Caporiacco, 1948) from Guyana; and Synema bishopi Caporiacco, 1955 from Venezuela. Synema bishopi is misplaced in this genus, but its correct placement is left for a future revision.